2014
DOI: 10.1016/j.nbd.2014.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear receptors in neurodegenerative diseases

Abstract: Nuclear receptors have generated substantial interest in the past decade as potential therapeutic targets for the treatment of neurodegenerative disorders. Despite years of effort, effective treatments for progressive neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, Huntington’s disease and ALS remain elusive, making non-classical drug targets such as nuclear receptors an attractive alternative. A substantial literature in mouse models of disease and several clinical trials have inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(107 citation statements)
references
References 177 publications
3
101
0
3
Order By: Relevance
“…Combination Therapy Increases apoE Particle Size in APP/ PS1 Mice-Previously published data indicate that increasing apoE protein levels and lipidation were associated with a reversal of the behavioral deficits and some aspects of pathology in AD mouse models (30). On the basis of our in vitro data indicating that combination therapy enhances the transcriptional effects of LXR and PPAR␥ agonists and their facilitation of A␤ degradation (Fig.…”
Section: Enhanced Effects Of Combined Activation Of Ppar␥ and Lxrmentioning
confidence: 51%
See 1 more Smart Citation
“…Combination Therapy Increases apoE Particle Size in APP/ PS1 Mice-Previously published data indicate that increasing apoE protein levels and lipidation were associated with a reversal of the behavioral deficits and some aspects of pathology in AD mouse models (30). On the basis of our in vitro data indicating that combination therapy enhances the transcriptional effects of LXR and PPAR␥ agonists and their facilitation of A␤ degradation (Fig.…”
Section: Enhanced Effects Of Combined Activation Of Ppar␥ and Lxrmentioning
confidence: 51%
“…Ligands that target peroxisome proliferator-activated receptor ␥ (PPAR␥) also produce increases in LXR target genes and the associated benefits, likely by inducing the expression of LXR␣ as well as interaction with enhancer elements (26 -28). A large body of literature indicates that activation of LXR, PPAR␥, or their heterodimeric partner RXR is able to ameliorate A␤ pathology and mediate behavioral improvements in mouse models of AD (29,30).…”
mentioning
confidence: 99%
“…Age-related neurodegenerative conditions have been linked to the disruption of cholesterol metabolism and LXR signaling (118). Likewise, LXR agonists have been shown to produce cognitive improvement in AD mouse models (121)(122)(123), but the mechanisms are not well understood. It has been suggested that the protective effects of LXR agonists are achieved by promotion of an increase in phagocytosis of amyloid-β by microglia (117), by inhibition of microglia nitric oxide synthetase (NOS) activity (124), or by attenuation of the microglia inflammatory response (125).…”
Section: R E V I E W S E R I E S : G L I a A N D N E U R O D E G E N mentioning
confidence: 99%
“…Nuclear receptors have been identified as potential therapeutic targets in AD. Indeed, agonists of nuclear receptors have been shown to reduce Aβ pathology and improve cognition in mouse models of AD (Skerrett et al 2014). Importantly, functional ABCA1 was necessary for the LXR agonist, GW3965, to reduce Aβ pathology and reverse deficits in novel object recognition (Donkin et al 2010).…”
Section: Introductionmentioning
confidence: 99%